Virus-Mediated Transient Expression Techniques Enable Functional Genomics Studies and Modulations of Betalain Biosynthesis and Plant Height in Quinoa - Ogata, Takuya; Toyoshima, Masami; Yamamizo-Oda, Chihiro; Kobayashi, Yasufumi; Fujii, Kenichiro; Tanaka, Kojiro; Tanaka, Tsutomu; Mizukoshi, Hiroharu; Yasui, Yasuo; Nagatoshi, Yukari; Yoshikawa, Nobuyuki; Fujita, Yasunari (Frontiers in Plant Science, 2021)
Quinoa (Chenopodium quinoa), native to the Andean region of South America, has been recognized as a potentially important crop in terms of global food and nutrition security since it can thrive in harsh environments and has an excellent nutritional profile. Even though challenges of analyzing the complex and heterogeneous allotetraploid genome of quinoa have recently been overcome, with the whole genome-sequencing of quinoa and the creation of genotyped inbred lines, the lack of technology to analyze gene function in planta is a major limiting factor in quinoa research. Here, we demonstrate that two virus-mediated transient expression techniques, virus-induced gene silencing (VIGS) and virus-mediated overexpression (VOX), can be used in quinoa. We show that apple latent spherical virus (ALSV) can induce gene silencing of quinoa phytoene desaturase (CqPDS1) in a broad range of quinoa inbred lines derived from the northern and southern highland and lowland sub-populations. In addition, we show that ALSV can be used as a VOX vector in roots. Our data also indicate that silencing a quinoa 3,4-dihydroxyphenylalanine 4,5-dioxygenase gene (CqDODA1) or a cytochrome P450 enzyme gene (CqCYP76AD1) inhibits betalain production and that knockdown of a reduced-height gene homolog (CqRHT1) causes an overgrowth phenotype in quinoa. Moreover, we show that ALSV can be transmitted to the progeny of quinoa plants. Thus, our findings enable functional genomics in quinoa, ushering in a new era of quinoa research.